Adoption of digital marketing among Bumiputera agropreneurs in Malaysia: the role of social influence, economic factors, convenience and facilitating conditions - Ahmad, Zulaiha; Tening Pahang, Josephine; Ya, Syazwani; Ibrahim, Ima Ilyani; Azizan, Farah Lina; Muhamat Anuar, Nur Assyura Zahirah (Universiti Teknologi MARA, Perlis, 2025)
Digital marketing promotes a seller's platform through digital technologies like websites, social media platforms, or mobile shopping apps. Marketers have increasingly adopted digital marketing to reach customers. In addition, the government also encourages business owners to incorporate digital marketing into their operations because it can significantly impact their business by helping them reach a wide range of customers both domestically and internationally. Therefore, the primary aim of this study is to examine the adoption of digital marketing among agropreneurs in Perlis. Survey questionnaires were distributed to 86 agropreneurs in Perlis using a simple random sampling approach. Results indicate that social influence, convenience and facilitating conditions are positively related to adopting digital marketing among agropreneurs in Perlis. This study concludes with several recommendations to help agropreneurs enhance their understanding and skills in adopting digital marketing strategies. Zulaiha Ahmad, Josephine Tening Pahang, Syazwani Ya, Ima Ilyani Ibrahim, Farah Lina Azizan, Nur Assyura Zahirah Muhamat Anuar